EMPOWERING CULTURAL COMMUNITIES IN PROTECTING TRADITIONAL EXPRESSIONS: LEGAL CHALLENGES IN THE DIGITAL AGE - Kholis Roisah; Rahayu Rahayu; Moh. Asadullah Hasan Al Asy'arie; Elena Mitskaya; Bryan Fayyadh Haq Wahyudi (Diponegoro Law Review, 2025)
Protecting Traditional Cultural Expressions (TCEs) is essential for safeguarding national identity and the values of communities that inherit and transmit cultural knowledge. This doctrinal study, grounded in comprehensive literature analysis, examines Indonesia’s regulatory framework and the practical challenges of TCEs protection. Research demonstrates that the limited positive influence on cultural holder communities' welfare stems from a noticeable dearth of clear technical policies outlining the institutions and systems for equitable benefit-sharing. The protection afforded to traditional cultural expressions (TCEs) is inherently twofold: it substantiates the importance of cultural diversity, spirituality, and religious practice while also functioning as an essential tool to preclude cultural plagiarism and inappropriate exploitation. The custodial  communities remain essential bearing the primary responsibility for maintaining, revitalizing, and transmitting local knowledge, artistic forms, and ritual practices. Concurrently, the digital era amplifies risks of misuse; specifically, the ease of digitization and rapid dissemination increase vulnerability to unauthorized appropriation and misrepresentation. To confront these risks, a combined approach is required, including positive and defensive measures within intellectual property regimes—such as tailored sui generis protections—alongside complementary policy instruments that emphasize community rights. Indonesia's legislative efforts, including the 2014 Copyright Law and the 2022 Government Regulation on Communal Intellectual Property (KIK), are compromised by major implementation deficits that undermine effective practical enforcement. The core argument here is for clearer, highly specific legal tools and stronger institutional arrangements that actively facilitate benefit-sharing and protect community interests. Ultimately, the study calls for a cohesive strategy that integrates protection with cultural-based economic growth and community empowerment to guarantee sustainable, intergenerational outcomes that preserve heritage while simultaneously lifting local welfare.